2018
DOI: 10.5607/en.2018.27.3.139
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Concept of Intrinsic Plasticity: Activity-dependent Modulation of Intrinsic Excitability in Cerebellar Purkinje Cells and Motor Learning

Abstract: What is memory? How does the brain process the sensory information and modify an organism's behavior? Many neuroscientists have focused on the activity- and experience-dependent modifications of synaptic functions in order to solve these fundamental questions in neuroscience. Recently, the plasticity of intrinsic excitability (called intrinsic plasticity) has emerged as an important element for information processing and storage in the brain. As the cerebellar Purkinje cells are the sole output neurons in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 154 publications
(222 reference statements)
0
40
1
2
Order By: Relevance
“…GCs generated a sparse representation of the MF inputs and they transmitted the encoded sensory information to 200 Purkinje cells (PCs), through excitatory projections. An intrinsic plasticity mechanism (Jang et al, 2020, Shim et al, 2018 regulated the excitability of model PCs, consistently with electrophysiological recordings (Shim et al, 2017, Turrigiano et al, 1994) (see Methods). PCs integrated the afferent signals from PFs (i.e., the axons of GCs), which elicited Purkinje simple spikes signal from climbing fibres (CFs), i.e., the axons of inferior olive (IO) cells.…”
Section: Cerebellar-dependent Vor Adaptationmentioning
confidence: 62%
See 1 more Smart Citation
“…GCs generated a sparse representation of the MF inputs and they transmitted the encoded sensory information to 200 Purkinje cells (PCs), through excitatory projections. An intrinsic plasticity mechanism (Jang et al, 2020, Shim et al, 2018 regulated the excitability of model PCs, consistently with electrophysiological recordings (Shim et al, 2017, Turrigiano et al, 1994) (see Methods). PCs integrated the afferent signals from PFs (i.e., the axons of GCs), which elicited Purkinje simple spikes signal from climbing fibres (CFs), i.e., the axons of inferior olive (IO) cells.…”
Section: Cerebellar-dependent Vor Adaptationmentioning
confidence: 62%
“…It has been suggested that neural compensatory retina slips during gaze stabilisation (i.e., error signalling), we evaluated to what extent age-related changes in the electrical coupling of inferior olive neurons could impact the VOR function. (ii) Intrinsic plasticity occurring at Purkinje cell synapses (Jang et al, 2020, Shim et al, 2018, which regulates the excitability of Purkinje neurons (by modulating their membrane capacitance) to adapt their response to synaptic morphological changes (Zhang et al, 2010, Andersen et al, 2003. We investigated the possible role of intrinsic plasticity at Purkinje cell synapses as a local homeostatic process, i.e., compensating for decreasing levels of vestibular afferent signals (which reach Purkinje cells through cerebellar granule cells) as well as for electro-responsiveness changes induced by ageing in Purkinje cells themselves (Zhang et al, 2010, Andersen et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Details are described in Materials and Methods. Lewis and Raman, 2014;Shim et al, 2018). Recent studies on the heterogeneous excitability among dendritic branches, through mechanisms underlain by BK, SK, and A-type K ϩ -channels (Rancz and Häusser, 2006;Ohtsuki et al, 2012b;Otsu et al, 2014;Ohtsuki and Hansel, 2018;Zang et al, 2018), argue against the uniform pattern of the intrinsic excitability of dendritic branches.…”
Section: Branch-specific Modulation Of the Intrinsic Excitability Undmentioning
confidence: 99%
“…Cerebellar PC intrinsic plasticity has been implicated as a neural computational feature of the information processing of cerebellar cortex (Belmeguenai et al, 2010;Grassi and Pettorossi, 2001;Shim et al, 2018Shim et al, , 2017Steuber et al, 2007). Notably, bidirectional modulation of synaptic plasticity at the PF-PC synapses has been found to be accompanied by intrinsic plasticity, which shows the same polarity with synaptic plasticity, indicating that the intrinsic plasticity might synergistically enable the PC spike output to be sufficiently modulated when synaptic plasticity occurs (Belmeguenai et al, 2010;Shim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has revealed that learning and memory is implemented not only by activitydependent synaptic plasticity but also by non-synaptic intrinsic plasticity in several neural circuits (Crestani et al, 2018;Lisman et al, 2018;Shim et al, 2018;Zhang and Linden, 2003). Of interest, intrinsic excitability contributes to integration of synaptic inputs and generation of net neuronal output (Hoffman et al, 1997;Lev-Ram et al, 2003, 1995Shim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%